Knygotyros klausimai 1904-1914 metų lietuviškoje spaudoje - Černiauskaitė, Violeta (Knygotyra, 1998)
New opportunities for professional background to various fields of the national culture and science emerged, when the prohibition against the Lithuanian press was lifted. The increasing attention to the history of language and literature with predominated patriotic propositions in a short time from 1904 to 1914 becomes more scientific and special in connection with urgent training or research interests. The evolution of writing and book history at that time was also directed by well-known tradition of biographical and bibliographical literary works, such as literary histories, prepared by Maironis, J. Gabrys and the most professional press analysis in "Prūsų lietuvių laikraščiai" (Lithuanian newspapers in Prussia) (1914) by A. Bruožis. The beginning of the rebirth of Lithuanian nation was the first time directly connected with the development of the national literature and book history facts in a historical review "Lietuvos atgijimas" ("The Revival of Lithuania", 1911) by S. Tijūnaitis.The most important contribution to the literary historiography progress made M. Biržiška with his efforts to describe and analyse literature history processes on a large scale of comprehensible historical-cultural context. The necessity to publish the full text of Catholic Bible translation and some continuous research activity in this field turned to the book history problems, which was more detailed discussed by J. Reitelaitis and J. Skvireckas.A great role in the determination of strategy for further book investigations and literary studies devoted to the Lithuanian Society of Education, founded in 1907. This Society published a first Lithuanian scientific periodical "Lietuvių Tauta", gathered much valuable archaeological, ethnographical material, collected old manuscripts, books, other documents and seeking for new methods of completing all Lithuanian editions in the library, arranged an extraordinary exhibition of almost 2500 publications from 1883 to 1914 and coordinated special program for ten year Lithuanian press anniversary, which primarily stimulated more active discussions on book study problems in press. The most significant material was published in "Viltis", "Lietuvos ūkininkas", "Lietuvos žinios", "Šaltinis" and other periodicals.A further fact of importance was special summary "Pirmutinės 10-ies metų spaudos atgavimo sukaktuvės" (1914), compiled by A. Jakštas-Dambrauskas, who wanted to emphasise most valuable works. An analysis of this publications indicated that a particular attention was given to the press ban situation in the second half of the 19th century, for such important facts of resistance as ignorance of books in Russian script and organization publication and distribution of abolished literature, especially noted the first Lithuanian newspaper "Aušra" for his outstanding service for a national movement.At the same time first general characterizations of the Lithuanian book publishing activity in 1904-1914 appeared among a great number of various publications in press, devoted to different problems of book editing, production, printing, distribution and reading. Taking into account, that the development of the Lithuanian press at the beginning of the XX century was called as "epidemic of newspapership", it becomes self-evident, why periodicals had been examined more intensive on historical, bibliographical, publishing, sociological and other subjects.Because of the competition for spheres of influence between opposite ideological positions represented in press, in a large number of literary and book study publications were reflected very different attitudes to the same historical and cultural events. But it should be pointed out, that during this time have been made first attempts to characterize book history and publishing processes to the full extent without chronological or territorial limits.